Internet of Things Implementation Analysis of Green Supply Chain Management in Companies - Ridhah, Habibatur; Sumarni, Nini; Siregar, Tika Rahmayani; Fitria, Fitria (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Supply chain management is an important part of achieving company efficiency. The existence of globalization makes the transformation of technology in supply chains. The use of IoT in enterprise operations makes the company grow quickly and more effectively and efficiently. But this kind of performance makes there is more energy consumption. Environmental problems such as global warming and increasing air pollution arise, so many studies have suggested improving Supply Chain Management (SCM) with Green Supply Chain Management. In this study, we wanted to discuss